Hubungan Motivasi Kerja dengan Kinerja Pegawai di Dinas Pendidikan, Pemuda dan Olahraga Kota Pariaman - Fadilatul Istiqamah; Irsyad Irsyad; Nelfia Adi; Tia Ayu Ningrum (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study aims to examine the relationship between work motivation and employee performance at the Pariaman City Education, Youth, and Sports Office. The study employs a quantitative approach using a correlational method. The study population consists of 80 employees, with a sample of 69 respondents selected using the Stratified Proportional Random Sampling technique based on the. The research instrument consisted of a questionnaire using a Likert scale that had been tested for validity and reliability. Data analysis techniques included descriptive analysis, normality tests, linearity tests, simple correlation analysis, and t-tests to test the research hypotheses. The results of the study indicate that employee performance falls into the “good” category with an average score of 4.10 and a percentage of 82%, while work motivation falls into the “high” category with an average score of 4.08 and a percentage of 82%. The results of the Product Moment correlation analysis show a correlation coefficient of 0.623, classified as strong and positive. Furthermore, the t-test results show that t-calculated = 6.511 > t-table = 1.668 with a significance level of 0.000 < 0.05. Thus, it can be concluded that there is a significant relationship between work motivation and employee performance at the Department of Education, Youth, and Sports of Pariaman City.